2009
DOI: 10.1186/1471-2458-9-419
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cost-Effectiveness in Obesity (ACE-Obesity): an overview of the ACE approach, economic methods and cost results

Abstract: BackgroundThe aim of the ACE-Obesity study was to determine the economic credentials of interventions which aim to prevent unhealthy weight gain in children and adolescents. We have reported elsewhere on the modelled effectiveness of 13 obesity prevention interventions in children. In this paper, we report on the cost results and associated methods together with the innovative approach to priority setting that underpins the ACE-Obesity study.MethodsThe Assessing Cost Effectiveness (ACE) approach combines techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 10 publications
5
135
0
2
Order By: Relevance
“…Previous studies have attempted to determine the potential long-term cost effectiveness of interventions aimed at treating overweight or obese children, but these studies have largely assessed interventions that have not been evaluated in RCTs. 12 However, without RCT evidence of public health effectiveness the meaning of the cost-effective analysis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attempted to determine the potential long-term cost effectiveness of interventions aimed at treating overweight or obese children, but these studies have largely assessed interventions that have not been evaluated in RCTs. 12 However, without RCT evidence of public health effectiveness the meaning of the cost-effective analysis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention costs in this study were lower compared with other similar intervention studies [10,22]. A study of a 3-year, after-school program to prevent obesity among elementary school students [10] reported the net intervention costs per capita was $317 and the achieved effectiveness was a 0.7% PBF reduction.…”
Section: The Costs Of the Interventionmentioning
confidence: 48%
“…Here, we discuss 2 areas that have been identified as strategies 6,[15][16][17][18] for cost-effective population-level change: taxes on sugary drinks and restrictions on marketing to children.…”
Section: Two Potentially Powerful Policiesmentioning
confidence: 99%
“…6 The Assessing Cost-Effectiveness (ACE) studies of obesity and of noncommunicable disease prevention identified the 3 most cost-effective policy interventions as a tax on unhealthy foods and beverages, a front-of-pack "traffic light" nutrition labeling system, and a reduction of marketing of unhealthy foods and beverages to children. 6,15,16 Recent reports from the Organization for Economic Cooperation and Development also support the idea that regulatory and fiscal policy could reduce obesity by improving defaults for the whole population. 17,18 The role of defaults in obesity prevention is presented visually in Figure 2, which is adapted from Swinburn and colleagues' recent article in The Lancet.…”
mentioning
confidence: 99%